Os caminhos da cultura digital: a emergência de novas práticas e enunciados políticos - Amaral, Vinícius Rodrigues Alvim (2012)
This thesis aims to analyze the changes in contemporary society, focusing on a study that aims to map and understand the actions of social movements in a society where the handling of information has become one of the most important means of capital accumulation. In this context, we analyze the changes in labor relations, driven by the rapidly increasing rate of production, computerization of factories, and the formation of a new way of working, the immaterial, which is the result of this process of change in production structure. Having a guiding principle as an approach to critical tradition, we seek to understand the unfolding of these new relations of production in society, as well as analyze the influence of social movements that take shelter in the scope of Digital Culture, as these movements are becoming a new alternative to social struggle in informational capitalism, which is becoming increasingly more predominant. Therefore, this study essentially aims to understand social movements and political work in informational capitalism, and the importance of this newly-emerging concept of digital culture